1983
DOI: 10.1111/j.1432-1033.1983.tb07494.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Studies of Aminoglycoside Acetyltransferase and Phosphotransferase from Staphylococcus aureus RPAL

Abstract: In the Staphylococcus aureus strain harbouring the plasmid RPAL, the resistance to aminoglycoside antibiotics results from two inactivating reactions catalyzed by a 6′‐N‐aminoglycoside acetyltransferase and a 2”‐O‐aminoglycoside phosphotransferase. These enzymes are copurified with a constant ratio between the two activities, the purification process consisting in affinity chromatography, native electrophoresis and gel exclusion chromatography. The kinetic mechanisms of each activity have been determinated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 16 publications
4
50
0
Order By: Relevance
“…GTP as the Phosphate Donor-Steady-state kinetic studies of the bifunctional AAC(6Ј)-Ie/APH(2Љ)-Ia and the monofunctional APH(2Љ)-Ia enzymes have demonstrated a selectivity for GTP (K m ϭ 3 and 3.5 M, respectively) over ATP (K m ϭ 3600 and 870 M, respectively) as the phosphate donor (9,10). Whether this preference manifests itself in vivo has yet to be explored.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GTP as the Phosphate Donor-Steady-state kinetic studies of the bifunctional AAC(6Ј)-Ie/APH(2Љ)-Ia and the monofunctional APH(2Љ)-Ia enzymes have demonstrated a selectivity for GTP (K m ϭ 3 and 3.5 M, respectively) over ATP (K m ϭ 3600 and 870 M, respectively) as the phosphate donor (9,10). Whether this preference manifests itself in vivo has yet to be explored.…”
Section: Resultsmentioning
confidence: 99%
“…These members of the aminoglycoside 2Љ kinase subfamily share only 28 -32% amino acid sequence identity among themselves and the APH(2Љ) domain of the bifunctional enzyme (8). We and others have shown that APH(2Љ)-IIa and -IVa have comparable relative affinities for both ATP and GTP, whereas the two others preferentially bind GTP, an indication that GTP and not ATP is the physiological cosubstrate for these enzymes (9,10). Contrary to what has been reported for the APH(2Љ)-Ia domain of the bifunctional enzyme, our kinetic characterization of APH(2Љ)-IIa, -IIIa, and -IVa demonstrated that 4,5-disubstituted antibiotics and the atypical aminoglycoside neamine are not substrates, but inhibitors of these enzymes (11)(12)(13).…”
mentioning
confidence: 99%
“…APH(2 00 )-IVa operates via a sequential mechanism in which the two substrates (NTP and aminoglycoside) bind in a random manner. All aminoglycoside-modifying enzymes studied to date (APH(3 0 )-Ia, APH(3 0 )-IIa, APH(2 00 )-Ia, APH(2 00 )-IIa, and APH(2 00 )-IIIa) operate via the sequential mechanism, 21,23,[26][27][28][29][30][31][32][33] and use a random mechanism for turnover chemistry, 21,23,31,33,34 with the exception of APH(3 0 )-IIIa, which has been shown to use a Theorell-Chance mechanism with compulsory ordered substrate binding and product release. 35 …”
Section: Kinetic Mechanism Of Aph(2 00 )-Ivamentioning
confidence: 99%
“…Solvent Viscosity and Solvent Isotope Effects for AAC(6Ј)-Ie-AAC(6Ј)-Ie has previously been shown to follow a random order Bi Bi kinetic mechanism (23). To further define the kinetic mechanism, we performed solvent viscosity effect (SVE) experiments with glycerol as the microviscosogen to identify the rate-determining step(s) in the catalytic cycle.…”
Section: Aac(6ј)-ie Can Acetylate Aminoglycoside 6ј-oh and 6ј-nh 2 -Amentioning
confidence: 99%
“…17). The kinetic mechanisms of characterized superfamily members (18 -22), including AAC(6Ј)-Ie (23), are sequential Bi Bi suggesting that acetyl transfer occurs directly from acetylCoA to acceptor substrate via the formation of a ternary enzyme⅐acetyl-CoA⅐aminoglycoside complex. Crystal structures of Tetrahymena GCN5 (tGCN5) histone acetyltransferase bound with acetyl-CoA and histone H3 (24) and serotonin N-acetyltransferase (also known as arylalkylamine N-acetyltransferase or AANAT) bound with a bisubstrate analog (25)(26)(27)(28), further argue for a direct acetyl transfer mechanism.…”
mentioning
confidence: 99%